A Briefing Note on the Port Sector in Bangladesh - World Bank (Washington, DC, 2013)
Traffic at Chittagong Port, which handles 90 percent of Bangladesh's foreign trade, has been growing rapidly. The volume of containers handled has increased by over 10 percent a year over the last decade and a similar or faster growth rate is projected for the foreseeable future. Chittagong Port has not responded to this demand growth effectively, resulting in congestions and delays at the port, as well as high costs to port users. The delays and uncertainties in port services seriously undermine the economy's productivity and international trading links. Improving both port operations and on-ward inland transportation system will be fundamental to maintain and improve the international competitiveness of the Bangladesh economy. The productivity at Chittagong port is the lowest among major ports in the region by most measurements. The impact of low productivity in Chittagong port is made worse by the poor inland transport distribution system for containers in the country. Chittagong port is the only major port in South Asia that has no private sector operator in its terminal operations and much of the port's services are run by public monopoly, thus limiting competition and reducing efficiency.